2018
DOI: 10.1519/jsc.0000000000002371
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plyometric and Directional Training on Speed and Jump Performance in Elite Youth Soccer Players

Abstract: Beato, M, Bianchi, M, Coratella, G, Merlini, M, and Drust, B. Effects of plyometric and directional training on speed and jump performance in elite youth soccer players. J Strength Cond Res 32(2): 289-296, 2018-Soccer players perform approximately 1,350 activities (every 4-6 seconds), such as accelerations/decelerations and changes of direction (CODs) during matches. It is well established that COD and plyometric training have a positive impact on fitness parameters in football players. This study analyzed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
109
4
26

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(155 citation statements)
references
References 30 publications
16
109
4
26
Order By: Relevance
“…These exercises would have contributed to shortening the sprint record by increasing force and power of the athletes. A few recent studies reported that plyometric training is effective to improve sprint performance [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…These exercises would have contributed to shortening the sprint record by increasing force and power of the athletes. A few recent studies reported that plyometric training is effective to improve sprint performance [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…It is well know that horizontal and vertical jump performances represent lower limb power and are pre-requisites for many sporting actions (8,22). Moreover, change of direction (COD) tasks are a critical component for team sports, since players need to perform many shuttle running activities during a match (2,9,35). Thus, the aims of the present study were: firstly to evaluate the time window effects of PAP following an EOL exercise (half squat) vs.…”
Section: Introductionmentioning
confidence: 99%
“…As such, more knowledge of how to improve the COD performance is of great importance to sport and conditioning coaches. Several studies have utilized strength training [14][15][16][17][18][19][20], specific COD drills [21][22][23][24][25], plyometric training [26][27][28][29] and a combination of these different training forms [30][31][32][33][34][35] to the physical aspect of COD performance [9].…”
Section: Introductionmentioning
confidence: 99%